Corruption in the Distribution of People’s Business Credit, Legal Enforcement and Accountability Analysis.docx - Yahya Boudelo; Ismail, Dian Ekawati; Rahim, Erman I. (Journal of Law and Policy Transformation, 2025)
This study aims to examine the Enforcement of Criminal Law Against Corruption in the Provision of People's Business Credit Facilities in Bone Pantai and the Accountability of BRI Management in Corruption in the Provision of People's Business Credit Facilities in Bone Pantai. The type of research used is normative legal research and empirical legal research. Empirical normative research starts from primary/basic data, and is then linked to law enforcement and criminal liability in corruption crimes in KUR. The results of this study indicate that criminal law enforcement against corruption in the provision of people's business credit facilities in Bone Pantai has not been implemented optimally and efficiently due to several weaknesses and problems that are obstacles in eradicating corruption and the involvement of internal bank figures and related parties by carrying out the mode of corruption of People's Business Credit (KUR) at Bank Rakyat Indonesia (BRI) Bone Pantai Unit involving data engineering. The accountability of BRI management in corruption crimes in the provision of people's business credit facilities in Bone Pantai shows that state losses are accounted for by the legal subject or defendant and the accountability of BRI bank, namely the head of the unit and the credit manager. The implementation of business ethics is very important in the distribution of KUR to ensure that the funds distributed are right on target to eligible recipients. Therefore, it is necessary to increase transparency in decision-making and credit distribution and increase the capacity of law enforcement regarding the handling of corruption cases involving people's business credit facilities (KUR).